"Even crap can be fertilizer": The experience of volunteering at sexual assault crisis centers for women survivors of sexual assault. (May 2021) - Gueta, Keren; Cohen-Leibovich, Yael; Ronel, Natti
This qualitative study illuminates the experience of volunteering at sexual assault crisis centers among women survivors of sexual assault. In-depth interviews were conducted with 11 women who had been volunteering at four different sexual assault crisis centers across Israel for 1 to 17 years. The findings reveal three main themes. First, there are five types of motivation to volunteer at such centers, all grounded in the participants' experience of sexual assault. Second, volunteering fosters recovery by promoting an empowered identity reconstruction and social integration. Third, both challenges and risks to recovery, such as exposure to sexual-assault triggers, arise from the experiences of sexual assault and volunteering at the centers. Moreover, the findings indicate various mechanisms that shape the risks–benefits dynamic involved in volunteering, such as the demands of the volunteering role. Thus, this study shifts the understanding of prosocial behavior by sexual-assault survivors from a binary assessment of "positive" or "negative" to a more comprehensive appraisal at the individual, role, and organizational levels.